Psychological Skill Training Implementation to Improve Football Referee Decision-Making Skills - Mochamad Yamin Saputra; Herman Subarjah; K Komarudin; Yusuf Hidayat; Yudi Nurcahya (Universitas Pendidikan Indonesia, 2022)
This study aimed to determine the impact of psychological skill training (PST) on football referee decision-making skills. The samples of the study were 12 referees with national football licenses. The samples joined the psychology skill training (PST) program for 12 meetings. The psychology skill training (PST) program carried out in this study included goal setting, self-talk, imagery, and relaxation. To find out the improvement of football referees' decision-making skills, the decision-making model of Samuel, Tenenbaum, Galily (2020) was used. The study results showed that psychology skill training (PST) improved football referee decision-making skills (72%). Thus, the PST model significantly influences football referees' decision-making skills. Therefore, it concludes that the psychology skill training (PST) model can be used as a solution for improving the decision-making skill of football referees.